PROBLEMATIKA PEMBELAJARAN BAHASA ARAB DI SDIT DARUS SUNNAH SUMBAWA - Muhammad Thoriq Nofiansyah; Zaki Yamani; Mubarak Bamualim (STAI Ali bin Abi Thalib Surabaya, 2022)
This study aims to describe how the problems of learning Arabic at SDIT Darus Sunnah Sumbawa are. The research method used in this research is descriptive qualitative. The research instrument used is interview, observation, and document review. The results of the study show that: (1) Arabic learning at SDIT Darus Sunnah Sumbawa, both from the linguistic and non-linguistic aspects, is still experiencing various problems from the teacher's and students' perspective. This is because the Arabic language teachers are still not at the level of quality they should be, most of the students do not have basic knowledge of reading and writing Arabic, as well as learning methods that are not in accordance with the students' marhalah. (2) Efforts to overcome the problems of learning Arabic at SDIT Darus Sunnah Sumbawa are by rearranging the curriculum which is expected to be in accordance with the level of understanding of students according to their age level, paying great attention to the ability to read the Qur'an, also by utilizing various interesting learning media in order to raise the morale and motivation of students.